2012
DOI: 10.1111/j.1743-7563.2011.01498.x
|View full text |Cite
|
Sign up to set email alerts
|

Mortality within 30 days of receiving systemic anti‐cancer therapy at a regional oncology unit: What have we learned?

Abstract: Our local outcome data are comparable to limited current international data. This type of audit reviews local outcomes and identifies factors contributing to mortality in order to improve standards of care. We encourage similar audits to establish national benchmarks of 30-day mortality rate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
35
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(41 citation statements)
references
References 12 publications
4
35
2
Order By: Relevance
“…Our audit demonstrated the feasibility of 30‐day mortality as an indicator for accessing quality in real‐life practice in a regional outpatient oncology unit in New Zealand. This study is unique as it audited 30‐day mortality over 5 years, as opposed to other contemporary studies, which chose shorter time frames (6–18 months) …”
Section: Discussioncontrasting
confidence: 68%
See 2 more Smart Citations
“…Our audit demonstrated the feasibility of 30‐day mortality as an indicator for accessing quality in real‐life practice in a regional outpatient oncology unit in New Zealand. This study is unique as it audited 30‐day mortality over 5 years, as opposed to other contemporary studies, which chose shorter time frames (6–18 months) …”
Section: Discussioncontrasting
confidence: 68%
“…Studies in Japan, UK, Australia and the United States have been published in the last decade . These studies were performed in large oncological institutions and demonstrated feasibility.…”
Section: Introductionsupporting
confidence: 67%
See 1 more Smart Citation
“…included only epithelial malignancies, Kao et al . excluded those with a haematological malignancy, Yoong et al . included all malignancies except acute leukaemia, Earle et al .…”
Section: Introductionmentioning
confidence: 99%
“…restricted inclusion to patients with advanced breast cancer. Most studies only included patients with advanced cancer; however, Yoong et al ., O'Brien et al . and Barbera et al .…”
Section: Introductionmentioning
confidence: 99%